Bringing The Incredible Years® Programs to Scale. Issue 149 (September 2015) - Webster‐Stratton, Carolyn; McCoy, Kathleen P.
Abstract: The Incredible Years ® (IY) program series is a set of interlocking and comprehensive training programs for parents, teachers, and children. This article briefly reviews the theoretical foundations, goals, and research underlying these programs. The main purpose of the paper is to describe how the IY programs have been scaled up slowly and carefully with fidelity by engaging in a collaborative building project with strong links between the developer, agency or school administrator, mentors, coaches, clinicians, and families using eight foundational building blocks or fidelity tools. © 2015 Wiley Periodicals, Inc.